2018
DOI: 10.12681/mms.15929
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology of urohyal bone in brackish water species of the genus Aphanius Nardo, 1827 in the Persian Gulf and Southeastern Mediterranean Sea basins (Teleostei: Aphaniidae)

Abstract: Among the skeletal elements in fishes, the urohyal bone which lies in the lower part of the head - the central part of the mandibular skeleton- has proved to be of special significance in fish systematics. The urohyal bone is considered to be a synapomorphic structure in teleostean fish. The urohyal bone of six brackish water Aphanius species (i.e., Aphanius hormuzensis, A. stoliczkanus, A. furcatus, A. ginaonis, A. mento, A. sirhani) was compared using morphological description and linear measurements to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
9
0
3
Order By: Relevance
“…Furthermore, our study revealed that the urohyal bone of A. hormuzensis is generally characterized by a moderately elongated and thickened basibranchial attachment (see Figure 15c). According to a comparative study by Teimori, Motamedi, and Iranmanesh (2018), it can be concluded that this characteristic morphology is typical for the brackish water species of Aphanius.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, our study revealed that the urohyal bone of A. hormuzensis is generally characterized by a moderately elongated and thickened basibranchial attachment (see Figure 15c). According to a comparative study by Teimori, Motamedi, and Iranmanesh (2018), it can be concluded that this characteristic morphology is typical for the brackish water species of Aphanius.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, several authors have documented that morphological characteristics related to hard structures can provide important taxonomic and phylogenetic information in Aphanius species, the studied hard parts included scales (Gholami, Teimori, Esmaeili, Schulz-Mirbach, & Reichenbacher, 2013;Teimori, 2018;Teimori, Motamedi, & Manizadeh, 2017), the urohyal bone (Teimori, Motamedi, & Iranmanesh, 2018), jaw teeth (Teimori, Esmaeili, Erpenbeck, & Reichenbacher, 2014), and otoliths (e.g., Reichenbacher, Sienknecht, Küchenhoff, & Fenske, 2007;Reichenbacher, Kamrani, Esmaeili, & Teimori, 2009;Teimori et al, 2012;Teimori, Esmaeili, et al, 2018).…”
mentioning
confidence: 99%
“…fasciatus groups. Parenti [28], has been summarized several diagnostic features for Aphanius mento (now Paraphanius mento) that are not found in the members of Aphanius and Aphaniops, including a cartilaginous interhyal (ossified in Aphanius and Aphaniops), an embedded urohyal (not embedded in Aphanius and Aphaniops, see also Teimori et al [59]), an upturned lower jaw (not upturned in other Aphanius and Aphaniops), and a distinctive neuromast pattern on the dorsal surface of the head (less prominently developed in Aphanius and Aphaniops species). Therefore, she proposed A. mento as a derived member of the Aphanius-like clade that should be designated as "Aphanius".…”
Section: Taxonomic Remarks On the Genera Aphanius Aphaniops And Parmentioning
confidence: 99%
“…Synonym of Lebias Goldfuss 1820, according to Lazara [30,26]. Valid as Aphanius Nardo 1827, according to Tortonese [31], Parenti [28], Wildekamp et al [32], Coad [33], Kruppand Schneider [34], Wildekamp [16], Poll & Gosse [35], Seegers [36], Wildekamp et al [23], Doadrio et al [37], Huber [38], Blanco et al [39], Hrbek et al [40], Kottelat et al [41], Kottelat & Freyhof [42], Hertwig [43], Coad [44], Teimori et al [45], Esmaeili et al [46], Teimori et al [47], Esmaeili et al [19], Gholami et al [48], Keivany & Esmaeili [49], Esmaeili et al [50], Teimori et al [51], Pfleiderer et al [52], Huber [53], Jouladeh-Roudbar et al [54], Esmaeili et al [55], Freyhof et al [9,10], Ç içek et al [56], Esmaeili et al [57], Golani & Fricke [58], Teimori et al [15,59], Yoğurtçuoğlu & Freyhof [60], Teimori & Motamedi [61], and Motamedi et al [62].…”
Section: Introductionmentioning
confidence: 99%
“…The urohyal bone is not easily digested in the stomach of predators; therefore, it has been used in trophic studies of the aquatic-and aquatic related animals such as fish, seals and birds (Hansel et al, 1988;Pierce et al, 1991;Johdal et al, 2001;Tombari et al, 2010). Moreover, owing to its morphological variability, the urohyal bone has been used extensively in fish taxonomy for species identification and even the discrimination among the genera and families (e.g., Kusaka, 1974;Pierce et al, 1991;Esmaeili & Teimori, 2006;Jawad et al, 2017;Teimori et al, 2018).…”
Section: Introductionmentioning
confidence: 99%